Vaccination of chickens with SPI1-lon and SPI1-lon-fliC mutant of Salmonella enterica Serovar Enteritidis - Matulova, Marta; Havlickova, Hana; Sisak, Frantisek; Rychlik, Ivan (PLoS One, 2013)
The prevalence of Salmonella enterica serovar Enteritidis is gradually decreasing in poultry flocks in the EU, which may result in the demand for a vaccine that allows for the differentiation of vaccinated flocks from those infected by wild-type S. Enteritidis. In this study, we therefore constructed a (Salmonella Pathogenicity Island 1) SPI1-lon mutant with or without fliC encoding for S. Enteritidis flagellin. The combination of SPI1-lon mutations resulted in attenuated but immunogenic mutant suitable for oral vaccination of poultry. In addition, the vaccination of chickens with the SPI1-lon-fliC mutant enabled the serological differentiation of vaccinated and infected chickens. The absence of fliC therefore did not affect the immunogenicity of the vaccine strain and allowed for serological differentiation of the vaccinated chickens. The SPI1-lon-fliC mutant is therefore a suitable marker vaccine strain for oral vaccination of poultry.
Keywords: bakteriální proteiny; Salmonella Vaccines; Salmonella enteritidis; protilátky bakteriální; Antibodies, Bacterial; Male; Chickens; salmonelová infekce u zvířat; Poultry Diseases; flagelin; mutace; Vaccination; kur domácí; nemoci drůbeže; Flagellin; Protease La; Bacterial Proteins; vakcinace; zvířata; mužské pohlaví; Mutation; proteasa La; Animals; salmonelové vakcíny; Salmonella Infections, Animal